How do you solve the equation 3x^2+6x=2x^2+3x-4 by completing the square?
1 Answer
Jul 10, 2017
x = -3/2 -sqrt(7)/2 \ i, -3/2 +sqrt(7)/2 \ i
Explanation:
We have:
3x^2+6x = 2x^2+3x-4
First let us collect terms on the LHS
3x^2 - 2x^2 + 6x - 3x -4 = 0
:. x^2 + 3x +4 = 0
Now we complete the square, by forming a term with half the "
:. (x + 3/2)^2 - (3/2)^2 +4 = 0
:. (x + 3/2)^2 - 9/4 +4 = 0
Which we can now re-arrange and solve;
:. (x + 3/2)^2 = -7/4
:. x + 3/2 = +-sqrt(7)/2 \ i
:. x = -3/2 +-sqrt(7)/2 \ i
Leading to the two complex conjugate solutions:
x = -3/2 -sqrt(7)/2 \ i, -3/2 +sqrt(7)/2 \ i
![]()